Dokimenische Säulensarkophage Datierung und Deutung / von Volker Michael Strocka ; mit einem Beitrag von Michael Wörrle ; Forschungsstelle Asia Minor im Seminar für Alte Geschichte der Westfälischen Wilhelms-Universität Münster. - Strocka, Volker Michael. (Asia Minor Studien, 2017)
The representative type of columnar sarcophagi in the Roman Empire came from Docimium, from workshops near its marble quarries. From there, they were distributed throughout Asia Minor, and in lesser numbers also exported to the Levant and to Italy. This study looks at the chronology and typology of columned sarcophagi from Docimium, beginning with an overview of the stone quarries of Docimium, looking at their products, transport routes, and trade processes. The second chapter examines a sarcophagus discovered in 1997 in the countryside surrounding ancient Tralleis (modern Aydın). Based on an associated inscription, it can be dated to 173 AD, making it the only columned sarcophagus dated by non-stylistic means. The third chapter explains the characteristics of columnar sarcophagi of the main type. In the fourth chapter, the chronology of sarcophagus types is checked and refined. The main type of sarcophagus with kline-lid was probably established shortly before the middle of the 2nd c. AD; the last pieces date to the end of the 3rd c. AD. Chapter 5 analyzes the iconography of all Docimian sarcophagi. Chapter 6 attempts to interpret the mythological and non-mythological as well as the seemingly merely decorative subsidiary motives of the columnar sarcophagi with regards to their allegoric references to death and the afterlife. Chapter 7 investigates the social standing of sarcophagus-owners or their families, based on inscriptions and grave monuments.This work also includes a list of 245 complete or fragmentary columned sarcophagus, their bibliography, and 98 plates with 269 illustrations.